2008
DOI: 10.1016/j.jsat.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in self-reported drug use by adolescents in substance abuse treatment: Implications for outcome and performance measurements

Abstract: This paper analyzes logical inconsistencies in adolescents' reporting of recent substance use to assess the potential effect of inaccurate reporting on measures of treatment outcomes and program performance. We used data from 1,463 clients at 10 adolescent treatment programs to assess the relationship between inconsistent reports and various factors that contribute to program assignment and treatment outcomes. Our results suggest that inconsistencies do not arise at random. Instead, inconsistencies were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
5
29
1
Order By: Relevance
“…Consistent with previous analyses of other survey data, in both editions of the PeNSE survey, we found that the prevalence of inconsistency was higher for males 45,53,54,55 , delayed students 56 , and those who reported having experimented with drugs 26,44,56 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous analyses of other survey data, in both editions of the PeNSE survey, we found that the prevalence of inconsistency was higher for males 45,53,54,55 , delayed students 56 , and those who reported having experimented with drugs 26,44,56 .…”
Section: Discussionsupporting
confidence: 91%
“…Self-reported substance use may be underreported. However, steps were taken to assure confidentiality of responses decreasing the likelihood of under-reporting (Harris, Griffin, McCaffrey, & Morral, 2008). Respondents were also given urine tests.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, people may exaggerate their amphetamine use to meet eligibility requirements for a program, be seen as rebellious, or impress an interviewer (Harrell, 1997; Macleod, Hickman, & Smith, 2005). Other reasons for inaccurate self-report data include: misunderstanding questionnaire items, memory failure, embarrassment about the topic, and not recognizing the drug terminology used on the questionnaire (Cottler et al, 1994; Harris, Griffin, McCaffrey, & Morral, 2008; Hser, Anglin, & Chou, 1992; Oullett, Cagle, & Fisher, 1997). The myriad reasons why respondents may unintentionally or intentionally provide inaccurate information about their drug use result in bias, through systematic under- and over-reporting, and to increased variability, through increased random error.…”
Section: Introductionmentioning
confidence: 99%